Emerging threat of candida resistance among neonates at a teaching institute of Jharkhand - Binita Biswas; Ashok Kumar Sharma; Kumari Seema; Abhay Kumar; Manju Boipai; Manoj Kumar* (Journal of Family Medicine and Primary Care)
Purpose: In the past few decades, candidemia has escalated to worrisome levels, leading to substantial morbidity and mortality in neonates. The rise in anti-fungal drug resistance demands prompt diagnosis and treatment. This study aimed to determine the speciation and susceptibility pattern of Candida species recovered from special care new-born units and identify risk factors for developing candidemia in neonates. Method: A total of 580 blood samples from clinically suspected septicemic neonates were collected and subjected to culture. Cultures positive for yeasts were sub-cultured on Sabouraud dextrose agar. Identification of a suspected purified colony of Candida was confirmed to the species level by both conventional and automated techniques matrix-assisted laser desorption and ionization time-of-flight mass spectrometry. Anti-fungal susceptibility of isolates was performed by an automated method (VITEK 2 system) using VITEK 2 cards. Multi-variate logistic regression analysis was used to identify risk factors associated with candidemia. Result: A total of 56 (9.66%) isolates of Candida species were recovered from 580 blood cultures. Non-albicans Candida species predominated with 82.14% of cases, whereas 17.86% of cases were caused by Candida albicans. Candida tropicalis (46.42%) was the most common isolate recovered, followed by Candida albicans (17.8%). Risk factor analyses identified a very low birth weight [odds ratio (OR) =4.05, 95% confidence interval (CI) =2.03–8.08] and prolonged antibiotic therapy (OR = 3.79, 95% CI = 1.7–8.7) among others as significant predictors of candidemia. All the Candida isolates showed 100% sensitivity to voriconazole and micafungin, whereas the overall sensitivities for fluconazole, amphotericin B, caspofungin, and flucytosine were 85.71%, 96.43%, 96.43%, and 91.07%, respectively. Conclusion: Candidemia is a life-threatening condition in neonates. Identification of Candida species and routine anti-fungal susceptibility is a must to select a suitable and effective anti-fungal therapy to revoke emerging resistance to anti-fungals.